Influence of Hemoglobin Level on Muscle and Physical Functions, Activities of Daily Living, and Quality of Life in Patients With Hematological Malignancies. (April 2019) - Fukushima, Takuya; Nakano, Jiro; Ishii, Shun; Natsuzako, Ayumi; Kawachi, Haruna; Sakamoto, Junya; Miyazaki, Yasushi; Okita, Minoru
Purpose. Patients with hematological malignancies often present with reduced muscle and physical functions, which are caused by the disease or related treatment. Moreover, patients with hematological malignancies rapidly develop low hemoglobin levels, and this may affect muscle and physical functions. This study aimed to identify the influence of hemoglobin levels on muscle and physical functions in patients with hematological malignancies. Methods. Using a cross-sectional study design, this study included 60 patients with hematological malignancies (mean age = 68.0 ± 10.2 years, women 56.7%) who were hospitalized for chemotherapy- and radiotherapy-related side effects and underwent examination for skeletal muscle mass (SMM), muscle strength, physical function, activities of daily living (ADLs), psychological status, and quality-of-life (QOL), including physical symptoms. Participants were divided into 3 groups according to tertiles of hemoglobin levels: low (n = 19), middle (n = 20), and high (n = 21). Evaluation items were compared among the 3 groups. Results. There was no significant difference among the 3 groups in terms of SMM. The low hemoglobin group showed significantly higher values of fatigue and dyspnea and lower values of muscle strength, ADLs, and QOL than the high hemoglobin group. Conclusions. Hemoglobin levels did not affect SMM; however, muscle weakness, decrease in physical function, physical symptoms such as fatigue and dyspnea, and decline in ADLs and QOL were observed in patients with low hemoglobin levels.